Pengaruh Pendidikan Budi Pekerti Terhadap Karakter Religius Siswa SMPN 2 Tegalsari Banyuwangi - Syahid, Mar (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
The formation ofreligious character is very important to be implemented in the realm of education, especially in schools to change the behavior of students who are not good will be good with akhlakul karimah. Realizing good and noble behavior needs to be held the formation of religious character. The result of the study there is a significant influence between Islamic religious education and manners, tolerance and sincerity of students SMPN from Tegalsari Banyuwangi. Based on the results of calculations that have been carried out shows that Islamic religious education and character significantly influence the religious character of peace-loving students at SMPN 2 Tegalsari Banyuwangi. It is shown by the research hypothesis that Ho is rejected and Ha is accepted. The meaning is, the better the learning of Islamic religious education and character related to the religious character of peace-loving religious, the greater the attitude of peace-loving behavior held by students at SMPN 2 Tegalsari Banyuwangi. And The meaning is, the better the learning of Islamic religious education and character related to the religious character of tolerance, the greater will the tolerance attitude possessed by students at SMPN 2 Tegalsari Banyuwangi.